2004
DOI: 10.1097/01.sap.0000122857.49274.8c
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical sRAGE in Diabetic Wounds Increases Neovascularization and Granulation Tissue Formation

Abstract: Advanced glycation end products (AGEs) accumulate in diabetic wounds as a result of the glycosylation of various proteins. Interaction of AGEs with the receptor for AGEs (RAGE) results in an exaggerated inflammatory response and compromised collagen production. These changes lead to impaired wound healing. A soluble form of RAGE (sRAGE) has been shown to bind AGEs and thereby blunt their pathogenetic effects. Using genetically diabetic C57BLks-db/db mice, the authors applied sRAGE topically to standardized ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Notably, treatment of the RAGE knockout mice with sRAGE offered no protection against asbestos-induced pulmonary fibrosis despite seeing the protein in the lung. This is in contrast to other RAGErelated disease processes, including atherosclerosis 25 and wound healing, 44 in which this dosage of sRAGE prevented disease. This suggests that the absence of mRAGE in the knockout mice may be the primary mediator contributing to pulmonary fibrosis in these mice.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, treatment of the RAGE knockout mice with sRAGE offered no protection against asbestos-induced pulmonary fibrosis despite seeing the protein in the lung. This is in contrast to other RAGErelated disease processes, including atherosclerosis 25 and wound healing, 44 in which this dosage of sRAGE prevented disease. This suggests that the absence of mRAGE in the knockout mice may be the primary mediator contributing to pulmonary fibrosis in these mice.…”
Section: Discussionmentioning
confidence: 85%
“…sRAGE, a synthetic version of a naturally occurring secreted form of the receptor that sequesters RAGE ligands, has been most studied in this regard. Administration of sRAGE was shown to suppress the growth of tumor cells in animal studies (6), improve outcomes in diabetes (11, 12), and block the transport of amyloid-β across the blood-brain barrier (13). These preclinical studies support the hypothesis that blocking RAGE activation will be useful as a treatment in a variety of pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble RAGE lacks the transmembrane domain, and is therefore released into the extracellular space. Since soluble RAGE retains the V-type domain, which is believed to be the principal site for ligand binding, soluble RAGE acts as a decoy receptor for RAGE ligands, inhibiting the activation of full-length RAGE by sequestering the RAGE ligands prior to their interaction with the RAGE receptor [Park et al, 1998;Thornalley, 1998;Schmidt et al, 2000Schmidt et al, , 2001 Bucciarelli et al, 2002a,b;Wear-Maggitti et al, 2004]. The least characterized form of RAGE is DNRAGE.…”
mentioning
confidence: 97%
“…This model proposes that S100 might increase the production of soluble RAGE from the osteoblastic cells. Among the six isoforms for RAGE, soluble RAGE has been shown to be able to suppress full-length RAGE activation by sequestering RAGE ligands before they encounter the membrane form of RAGE [Park et al, 1998;Bucciarelli et al, 2002a;Wear-Maggitti et al, 2004]. Hanford et al [2004] reported that soluble RAGE results from an alternative splicing of RAGE mRNA in humans, but soluble RAGE in the mouse results from a carboxyl-terminal truncation, suggesting that soluble RAGE isoform production would not be distinguishable from full-length RAGE at the level of mRNA expression.…”
mentioning
confidence: 97%